Jory Heyn: capstone - Heyn, Jory, artist (Colorado State University. Libraries, 2017)
The artist's statement: I'm an explorer. I want to explore what's new to me to obtain more tools in my repertoire of skills and knowledge. Searching for knowledge is a basic human instinct. We want to make sense of our world around us, make sense of who we are in this world, and how to interact with every aspect of what makes up our world. I began my journey with an interest of how humans, through the ages, have come to understand the stars and the universe. How ancient cultures personified the stars through constellations in conjunction to their Gods. How ancient cultures used the stars for navigation, in further understanding and exploring their worlds. How humans are still exploring space, and gaining more knowledge with the boom of technology. I grew attached to the ultra violet markers as a medium through this period of exploration. How marks that I'd make wouldn't be visible until reacted with an ultra-violet light source. How something could simultaneously exist, but seemingly not exist simultaneously. As I'd gained knowledge, I began to turn my focus away from the natural wonders of the world, but instead how I existed in this world. I began to explore how my experience shaped me into who I am today, and how these experiences may have occurred only in the way that they did, when they did, and where they did. How my losses and struggles have turned to strengths. How these losses, though each unique to me, is a shared sympathetic experience with humanity and how we still, gain knowledge through hard times.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images and video of works.
Video has no sound.
Keywords: drawing; capstone